2021
DOI: 10.1051/0004-6361/202141069
|View full text |Cite
|
Sign up to set email alerts
|

The Gaia-ESO Survey: a new approach to chemically characterising young open clusters

Abstract: Context. Young open clusters (ages of less than 200 Myr) have been observed to exhibit several peculiarities in their chemical compositions. These anomalies include a slightly sub-solar iron content, super-solar abundances of some atomic species (e.g. ionised chromium), and atypical enhancements of [Ba/Fe], with values up to ~0.7 dex. Regarding the behaviour of the other s-process elements like yttrium, zirconium, lanthanum, and cerium, there is general disagreement in the literature: some authors claim that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 131 publications
(152 reference statements)
4
21
0
Order By: Relevance
“…In their study of dwarf stars in five open clusters and one starforming region, Baratella et al (2021) found an enhancement in Ba similar to what we have found in our stars. Remarkably, Ba is more enhanced for the younger clusters.…”
Section: Mg Al and Casupporting
confidence: 91%
See 1 more Smart Citation
“…In their study of dwarf stars in five open clusters and one starforming region, Baratella et al (2021) found an enhancement in Ba similar to what we have found in our stars. Remarkably, Ba is more enhanced for the younger clusters.…”
Section: Mg Al and Casupporting
confidence: 91%
“…At face value, our derived [Y/Fe] abundance ratios are ∼ 0.2 dex, but we do not give much weight to the Y enhancement as it is consistent with [Y/Fe]=0 within the errors. Baratella et al (2021) examined several causes for this Ba anomaly, including the role of magnetic fields. They failed to propose any convincing explanation of their observations, however.…”
Section: Mg Al and Camentioning
confidence: 99%
“…The role of these stars in producing neutron-rich elements in the Galactic disk has been so far underestimated, and their evolution and neutron-capture nucleosynthesis should now be reconsidered. The most recent observations have confirmed that the young clusters appear to be extremely enhanced in Ba, but the other s-process elements are not enhanced (see e.g., recent work by [39] and references therein). This cannot be explained in terms of s-process nucleosynthesis, and the current explanations for this Ba excess range from observational problems with Ba to the presence of a neutron capture process intermediate between s-process and r-process.…”
Section: New S-process Yieldsmentioning
confidence: 90%
“…[38]. Filled triangles represent abundance measurements that probably need NLTE (non-local thermodynamic equilibrium) corrections (but see [39]). The model results are shown for two set of yields: the standard yields [4,7] with a long-dashed curve; the enhanced s-process yields with a dot-dashed curve.…”
Section: New S-process Yieldsmentioning
confidence: 99%
See 1 more Smart Citation